(untitled) (Ágora de Heterodoxias, 2015)
The center of the hegemonic management theories is, exactly, to train each individual as a subject of continuous self-control and annual balances, a subject that, in this way, creates for himself an intra-worldly experience, as Harald Welzer says, quoting Joseph Vogl: you cannot neither lose any time nor any act may be unproductive. Since the commercial success is identical to the biographical, the same parameters would be valid for both business and life. Therefore, the overcoming of the concentration of wealth and power rates, and the devastation of nature, with the purpose of a greater solidarity and sustainability, depends only if the judgment that determines the action have another source of epistemological, theoretical, methodological and experiential reference, given by Management Theory. The dualistic separation between psychism and institutions is not sustainable anymore because it is not emancipatory. Thus the author applied to the Management Theory its Psychopolitical Perspective of Social Theory.